Pyroelectric energy conversion using Ba0.85Sr0.15Zr0.1Ti0.9O3 ceramics and its cement-based composites. (April 2019) - Kumar, Anuruddh; Kumar, Sidhant; Patel, Satyanarayan; Sharma, Moolchand; Azad, Puneet; Vaish, Rahul; Kumar, Rajeev; Srikanth, KS
In this article, we focus on cement-binded Ba0.85 Sr0.15 Zr0.1 Ti0.9 O3 ceramics for pyroelectric applications. It was prepared with the Ba0.85 Sr0.15 Zr0.1 Ti0.9 O3 -to-cement ratios of 85%:15% and 80%:20% by weight. In order to improve the effectiveness of thermal-to-electric energy conversion, the synchronized switch harvesting on inductor technique is experimentally tested on cement composites. Our experimental findings reveal that this concept based on synchronized switch harvesting on inductor can significantly increase the amount of power extracted from pyroelectric materials. Furthermore, the optimized power across 15% and 20% cement composites were found to be 7.2 and 6 nW, respectively, in series synchronized switch harvesting on inductor and 8.5 and 7 nW, respectively, in parallel synchronized switch harvesting on inductor. These values are significantly higher when compared with non-switched circuit for pyroelectric applications. Although, from the obtained results for the prepared composites, the power output is less when compared with pure Ba0.85 Sr0.15 Zr0.1 Ti0.9 O3, they have some advantages: these composites can be made without any sintering process and are compatible for structural applications.